Granulosa cell tumor of the ovary: a clinicopathological study of six cases - Adhikari, RC; Jha, A; Shayami, G (Journal of Pathology of Nepal, 2011)
Background: Ovarian granulosa cell tumors are rare malignant neoplasms that originate from the sexcord stromal cells of the ovary. The study aims to collate data of all granulosa cell tumors diagnosed in Tribhuvan University Teaching Hospital over the last 3 years and to describe the incidence, patient profile, ultrasonographic and histopathologic findings in our local context. Materials and Methods: A total of 6 (5%) granulosa cell tumors, diagnosed in Tribhuvan University Teaching Hospital during the period from April 2008 to March 2011. The patient’s age, symptoms, radiological findings, type of surgery performed, tumor size and follow-up status were evaluated. Results: All 6 patients were diagnosed as adult granulosa cell tumor, three of which were postmenopausal (50%) and remaining there was premenopausal. The symptoms recorded were uterine bleeding, abdominal pain, distention and mass. Grossly, in 3 cases granulosa cell tumors were solid and firm, in 2 cases solid and cystic and 1 case is predominantly cystic. Histologically, variety of patterns including diffuse, trabecular, cords, tubular, nesting and Call-Exner bodies were found. Nuclear grooves were observed in all cases. Follow up on 2 patients revealed no evidence of recurrence. Conclusion: This study supports the view that most granulosa cell tumors are diagnosed in stage I and there is good correlation between radiological and gross findings in terms of tumor size and solid or cystic status. Keywords: Granulosa cell tumor; Ovary; Histopathological findings DOI: http://dx.doi.org/10.3126/jpn.v1i2.5400 JPN 2011; 1(2): 96-99